Counseling and Therapy - George Taukeni, Simon (IntechOpen, 2020)
This book, Counselling and Therapy, aims to equip students, life skills teachers, counselors, psychologists, academics, and other health practitioners with the most practical counselling and therapy basic skills, different counselling approaches, and problem-based techniques to address psychosocial problems. In this edition of Counselling and Therapy the following contents were covered: Definitions of counselling and therapy Counselling principles and theories Gender-based violence Self-efficacy and self-esteem Basic counselling communication skills